Serum profile of the anti-müllerian hormone of Nelore bulls in the peripuberty - Pereira, J. A.; Satrapa, R. A.; Gomes, M. G. T.; Moure, V. R.; Valdameri, G.; Kozicki, L. E.; Sousa, G. C.; Souza, F. F. [UNESP]; Laskoski, L. M.; Souza, F. A. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2024)
This study aimed to investigate the profile of AMH serum concentrations during the period of prepuberty in young bulls. The bulls were selected and evaluated for 150 days to assess their sexual development. The semen and blood collection, body weight (kg), and scrotal measurements were performed every 30 days, and puberty (D0) was considered when at least 50x10 6 spermatozoa/mL, and 10% of progressive motility were verified for the first time. After the blood collection, plasma was separated and used to determine the AMH concentration by ELISA, presenting values of 611.4a (+/- 94.5), 555a (+/- 181.99), 621.6ab (+/- 133.44), 370.4ab (+/- 59.36) and 51.7b (+/- 7.94) for moments of -60, -30, 0, +30 and +60 of puberty, respectively. During the evaluated period, there was a progressive increase in body weight (kg), scrotal circumference (cm), and semen characteristics. The AMH mean plasma concentration decreased 60 days after puberty onset. There was no correlation with the andrological parameters analyzed; however, there was a positive and strong correlation between the testicular height and width at puberty onset with plasma concentrations of AMH. We concluded that AMH is not a helpful tool for the early prediction of puberty in Nelore bulls.
Keywords: AMH; Bos indicus; puberty; younger bulls